Soil penetration resistence in coffe plantations cultivated with mechanized and manual systems - Zambillo Palma, Marcos Antonio; Silva Volpato, Carlos Eduardo; Castro da Silva, Flávio; de Souza, Pauliane; Silva, Jéssica Aparecida (Coffee Science - ISSN 1984-3909, 2014)
Coffee harvesting mechanization systems reduce production costs, however, there is the chance of soil physical degradation due to considerable increase of machinery traffic. The objective of the present study was to evaluate the soil resistance to penetration in two coffee plantation systems and was developed in the municipality of Tres Corações – MG, in a farming divided in two turfs: one where all of the cultivation treatments were performed mechanically and one other turf where the treatments were performed manually. Measurements were performed with the help of a digital penetrometer in the cultivation line, traffic line and in the center of the cultivation leadings. The conclusion was that the mechanized cultivation system presents greater soil resistance values to penetration down to 0,15m depths and les humidity, when compared to the manual cultivation system.